Digital Video Compression Using DCT-Based Iterated Function System (IFS) - Nevart A. Minas; Faten H. Al-Qadhee (Tikrit Journal of Pure Science)
Large video files processing involves a huge volume of data. The codec, storage systems and network needs resource utilization, so it becomes important to minimize the used memory space and time to distribute these videos over the Internet using compression techniques. Fractal image and video compression falls under the category of lossy compression. It gives best results when used for natural images.